Interpolation Approaches to Groundwater Quality Mapping: Trends and Techniques in Erbil City - Frsat Abdullah Ababakr; Shiva Shakeri; Edris Tand; Somayeh Kazemi (Advances in Civil Engineering and Environmental Science, 2024)
Population increases and climate change threaten the quality of groundwater. The objective of this study was to identify the most effective techniques for estimating and generating zoning maps of groundwater quality. Additionally, the research aimed to explore trends in groundwater quality changes over time and to analyze the spatiotemporal distribution patterns of these quality parameters. To do this, the groundwater quality parameters assessed included turbidity (TUR), pH, EC, total dissolved solids (TDS), total alkalinity (TA), total hardness (TH), Ca²⁺, Mg²⁺, Na⁺, K⁺, Cl⁻, NO₃⁻, and SO₄²⁻. Data was collected from 61 selected wells in Erbil City, Kurdistan, Iraq, during the wet and dry seasons from 2015 to 2018. The evaluation of different interpolation methods revealed that the Kriging method, except for TA, EC, and TDS, was more accurate than the Inverse Distance Weighting (IDW) method for zoning. Regarding water quality, all parameters, except for NO₃⁻, TA, and TUR in both wet and dry seasons, as well as K⁺ in the wet season and total TH in the dry season, were below World Health Organization standards. Time analysis indicates a relative increase in most parameters, underscoring the urgent need for comprehensive planning and management to address and improve the current situation.